2018
DOI: 10.1111/coa.13046
|View full text |Cite
|
Sign up to set email alerts
|

Results of a systematic literature review of treatment modalities for jugulotympanic paraganglioma, stratified per Fisch class

Abstract: An individual risk is constituted for surgery and radiotherapy, stratified per Fisch class. For class A and B tumours, surgery is a suitable treatment option. For class C and D tumours, radiotherapy results in lower complication rates and similar or better local control rates when compared to the surgical group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 37 publications
5
37
0
Order By: Relevance
“…As outlined above, radiotherapy seems to be the treatment of choice in general as it provides excellent local control and fewest complications. These results are in line with a systematic literature study conducted by our group, as outlined above . It was previously suggested that radiotherapy should be reserved for older patients due to the risk of induction of malignant tumours or cerebrovascular accidents .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As outlined above, radiotherapy seems to be the treatment of choice in general as it provides excellent local control and fewest complications. These results are in line with a systematic literature study conducted by our group, as outlined above . It was previously suggested that radiotherapy should be reserved for older patients due to the risk of induction of malignant tumours or cerebrovascular accidents .…”
Section: Discussionsupporting
confidence: 91%
“…Overseeing this and considering sequelae up to thirty years post‐treatment, we feel that radiotherapy as monotherapy is a viable option from the age of 50 years onwards . Please note that this suggestion is based on theoretical grounds, nevertheless, it is in line with suggestions of previous studies . Moreover, such severe and life‐threatening complications were not found in the current study after a follow‐up of 82 months (range 8‐182).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this context, conventionally fractionated RT and radiosurgery as SRS, FSRT, or HFSRT are now considered as a viable part of multimodality TBC management. While management of advanced, incompletely resected, or recurrent lesions with irradiation has been widely accepted as common practice, accumulating evidence in favor of irradiation has been supported by several studies as well as systemic reviews and metaanalyses assessing its utility as the primary mode of management [56, [63][64][65][73][74][75][76][103][104][105][106][107][108][109][110].…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic patients who are elderly or infirm may be observed. Surgery is an option for those with small PGs that can be completely excised with limited morbidity . Skull base PGs that are 3 cm or less may be treated with stereotactic radiosurgery (SRS) .…”
Section: Introductionmentioning
confidence: 99%